Communication and Interprofessional Collaboration in Primary Care: From Ideal to Reality in Practice. Issue 2 (28th January 2021) - Fox, Stephanie; Gaboury, Isabelle; Chiocchio, François; Vachon, Brigitte
ABSTRACT: To improve patient-centered care, many health care systems are mandating interprofessional collaboration (IPC). However, in many primary care contexts, IPC is still nascent and fraught with tension. Communication is thought to be a key determinant of IPC, but few studies empirically examine IP communication practices. Therefore, we report here on the qualitative portion of a mixed methods pilot study investigating observed IPC and communication in primary care clinics in Quebec, Canada. Studying actual communication practices to understand collaborative activities, we seek to investigate how the ideals of patient centeredness and clinical democracy put forward in the IP literature stack up against actual IPC practice in primary care. Qualitative data was gathered by shadowing health professionals in two primary care clinics, and analyzed through thematic coding. A typology of observed IP practices was created and compared to the continuum of interprofessional collaborative practice. Further analysis focused on how participants made sense of their collaboration, especially why, how and with whom they collaborated. Findings were grouped into three categories of communicative actions: coordinating sequential efforts; assisting others' sensemaking; and working to understand together. Implications for practice and future research are discussed.